Analisis Faktor - Faktor Internal yang Mempengaruhi Loyalitas Karyawan pada CV. X - Tra Kaca & Aluminium Surabaya - Munadzifah, Fiya; Fahrullah, A'rasy (Universitas Negeri Surabaya, 2021)
Loyalty to the company affects the performance of employees in their activities. So companies need to maintain employee loyalty. Many factors make employees have a loyal attitude towards the company such as compensation, Islamic organizational culture, job satisfaction, career development, Islamic leadership and religiosity. This study aims to analyze the internal factors that affect employee loyalty at CV. X-Tra Glass & Aluminum Surabaya. This research is a quantitative study of 179 employees and a sample of 69 employees. The data collection method uses a questionnaire or questionnaire with measuring instruments using the Likert scale. Data analysis using multiple linear regression, partial test (T), simultaneous test (F) and coefficient of determination (R2) test using the SPSS application. The results of multiple linear regression analysis show the compensation regression coefficient is 0.306, Islamic organizational culture is -2.488E-5, job satisfaction is 0.465, career development is -0.192, Islamic leadership is 0.272, religiosity is -0.397. The results of the T test show that there is an influence on loyalty to the variables of Islamic organizational culture, job satisfaction and religiosity.There is no influence on loyalty to the variables of compensation, career development, Islamic leadership. F test result show that the independent variables have a simultaneous influence on loyalty. While the R2 test result are at the velue at the value of 0.858, which means that the variable affects loyalty a lot and 0.142 is influenced by other variables.